Analysis Of Surface Deformation Due To The Manay Earthquake, Philippines, Using The Interferometric Synthetic Aperture Radar (InSAR) Method Based On Sentinel-1c Data - Habibillah Alva Putra Alva; Pakhrur Razi (GeoREST, 2026)
The Philippines is one of the most tectonically active regions in the world, situated at the convergence of several major and minor plates, including the Philippine Sea Plate, the Sunda Plate, and the Eurasian Plate. This complex tectonic setting makes the archipelago highly susceptible to frequent and often destructive earthquakes, which can trigger significant deformation of the ground surface, infrastructure damage, and secondary hazards such as landslides and liquefaction. One notable seismic event occurred in the Manay region, Mindanao, Philippines, generating measurable surface displacement that requires accurate spatial assessment for effective disaster response and mitigation planning. However, ground-based monitoring alone is often insufficient to capture the spatial extent and pattern of coseismic deformation, particularly in remote or rapidly affected areas. This study addresses this gap by employing the Interferometric Synthetic Aperture Radar (InSAR) technique to analyze surface deformation associated with the Manay earthquake, utilizing Sentinel-1C Single Look Complex (SLC) imagery. Pre-event and post-event SAR acquisitions were processed to generate interferograms, phase decomposition, and line-of-sight surface displacement maps. The InSAR approach enables wide-area deformation monitoring with high spatial resolution and centimeter-level accuracy, offering advantages over conventional in-situ measurement techniques. The resulting deformation maps reveal the spatial distribution and magnitude of ground displacement induced by the earthquake. These findings are expected to enhance the understanding of coseismic surface behavior in tectonically active regions and to serve as a valuable reference for future disaster risk assessment, seismic hazard mapping, and mitigation strategies in the Philippines and similar geodynamic settings.